2020
DOI: 10.1073/pnas.2000078117
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of plant quantitative disease resistance is provided by a decentralized immune network

Abstract: Quantitative disease resistance (QDR) represents the predominant form of resistance in natural populations and crops. Surprisingly, very limited information exists on the biomolecular network of the signaling machineries underlying this form of plant immunity. This lack of information may result from its complex and quantitative nature. Here, we used an integrative approach including genomics, network reconstruction, and mutational analysis to identify and validate molecular networks that control QDR in Arabid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 52 publications
1
69
0
Order By: Relevance
“…Protein phosphorylation occurs during kinase signalling processes. A predominant role of genes related to metabolism as well as kinase-signalling cascades for QDR has been proposed before (Delplace et al 2020). Taken together, this suggests that maize line-specific responses to U. maydis involved various cellular activities, consistent with the complex nature of QDR.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Protein phosphorylation occurs during kinase signalling processes. A predominant role of genes related to metabolism as well as kinase-signalling cascades for QDR has been proposed before (Delplace et al 2020). Taken together, this suggests that maize line-specific responses to U. maydis involved various cellular activities, consistent with the complex nature of QDR.…”
Section: Resultsmentioning
confidence: 97%
“…In general, QDR can be hypothesised as an intricate network integrating various response pathways to pathogen determinants and environmental factors (Roux et al 2014). Additionally, studies of QDR by RNA-Seq approaches have indicated highly interconnected and multifaceted defence responses, which were mostly distinct from functions previously identified for plant immunity (Kebede et al 2018; Pan et al 2018; Delplace et al 2020).…”
Section: Introductionmentioning
confidence: 92%
“…Protein phosphorylation occurs during kinase signalling processes. A predominant role of genes related to metabolism as well as kinase signalling cascades for QDR has been proposed before (Delplace et al ., 2020). Together, this suggests that maize line‐specific responses to U. maydis involve various cellular activities, consistent with the complex nature of QDR.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, compared to qualitative resistance, the molecular functions underlying QDR seem to be highly diverse. Additionally, studies of QDR by RNA sequencing (RNA‐Seq) approaches have indicated highly interconnected and multifaceted defence responses, which were mostly distinct from functions previously identified for plant immunity (Delplace et al ., 2020; Kebede et al ., 2018; Pan et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Even if it is considered the predominant resistance found in nature, genes and mechanisms involved in QDR are poorly understood (Bartoli and Roux, 2017;Delplace et al, 2020), and resistance involving the QDR is more difficult to select due the involvement of several genes (Corwin and Kliebenstein, 2017). Because of the reduced selective pressure on the pathogen and the possibility of providing broad-spectrum resistance for more than one species and/or race of a pathogen, QDR has great potential to be more durable in the field (Krattinger et al, 2009;Corwin and Kliebenstein, 2017;Pilet-Nayel et al, 2017;Nelson et al, 2018).…”
Section: Introductionmentioning
confidence: 99%